UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGY IN THE LEARNING PROCESS IN THE DIGITAL ERA - Maya Sari (International Journal of Teaching and Learning, 2025)
This literature research aims to examine in depth the use of Information and Communication Technology (ICT) in the learning process in the digital era. With a focus on the integration of various digital tools and platforms in education, this research identifies how ICT can increase engagement, accessibility and personalization of learning. The methods used include surveys of educators and students, case analysis of classes that have implemented this technology, as well as a review of relevant literature. The research results show that ICT facilitates more flexible and adaptive learning, encourages more effective collaboration between students and teachers, and increases ease of access to learning materials from anywhere and at any time. Furthermore, these findings show that the use of informative and communicative technology helps in adapting learning material to individual student needs, thereby increasing learning effectiveness. This research concludes that ICT plays a crucial role in redefining educational methods, making them more relevant to the needs of today's digital era. Proper implementation of ICT in education not only improves the quality of learning but also prepares students with the skills necessary for the future in an increasingly technology-based world.